2020
DOI: 10.31234/osf.io/mpxra
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying smartphone ‘use’: Choice of measurement impacts relationships between ‘usage’ and health

Abstract: Self-report dominates research that considers the impact of technology on people and society. However, errors of measurement may obscure any genuine associations between technology use and mental health. We explored how different ways of measuring technology use, through psychometric scales, subjective estimates and objective logs leads to highly distorted associations between screen-time and health. Across two pre-registered designs, including: iPhone (n=199) and Android (n=46), we observed that measuring sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Therefore, when researchers rely on self-reports of play behaviour to test relations with mental health, measurement error and potential bias will necessarily lead to inaccurate estimates of true relationships. Previous work has shown that using self-reports instead of objective measures of technology use can both inflate [ 45 , 46 ] or deflate effects [ 44 ]. In our study, associations between objective play time and well-being were larger than those between self-reported play time and well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when researchers rely on self-reports of play behaviour to test relations with mental health, measurement error and potential bias will necessarily lead to inaccurate estimates of true relationships. Previous work has shown that using self-reports instead of objective measures of technology use can both inflate [ 45 , 46 ] or deflate effects [ 44 ]. In our study, associations between objective play time and well-being were larger than those between self-reported play time and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…[43]) associations between video game play time and psychological functioning. For example, studies suggest that self-reported technology use can lead to both overestimates and underestimates of the association with well-being compared to directly logged technology use [44][45][46]. Therefore, our scientific understanding of video game effects is limited by our measures.…”
Section: Video Game Behaviour and Well-beingmentioning
confidence: 99%
“…In regard to our measures, a recent study (Shaw et al, 2020) illustrated that self-reports of media use tend to inflate relationships with psychological well-being variables, compared to unobtrusive tracking of device usage. We attempted to mitigate the limitations of self-reported media use by asking participants about a variety of specific media platforms, and asked them to report average daily hours for each platform in the context of social distancing, however we note this as a limitation.…”
Section: Limitationsmentioning
confidence: 99%
“…A second study then acted as a replication and provided increased statistical power. All materials for both studies are located on the Open Science Framework (see Shaw, Ellis, Geyer, et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%